Quality Of Life In Children With Type 1 Diabetes: Family And Health Care Professionals’ Perspectives. - Totala, Parvi; Kumar Garg, Hemant; Singh, Brij Mohan (Journal of Neonatal Surgery, 2025)
Background: Type 1 diabetes mellitus (T1DM) is a chronic condition that affects children’s physical, emotional, and social well-being. Understanding quality of life (QoL) from both family and health care professionals’ perspectives is essential for holistic management. Objective: To evaluate the QoL of children with T1DM aged 5–18 years, as perceived by parents and nurses, and to identify areas of agreement and divergence between these perspectives. Methods: A cross-sectional descriptive study was conducted involving 24 children with T1DM. Parents completed a 15-item Likert-scale questionnaire covering five domains: physical well-being, emotional well-being, social functioning, family impact, and health care support. Additionally, 100 nurses working in pediatric diabetes care completed the same questionnaire based on their professional observations. Data were analyzed using descriptive statistics, domain averages, and comparative visualizations (bar charts, pie charts, line plots, box plots, and scatter plots). Results: Parents reported higher emotional distress and social limitations compared to nurses. Nurses emphasized medical adherence and resilience, particularly in older children. Both groups acknowledged family stress and the importance of health care support. Conclusion: Parents and nurses perceive QoL in children with T1DM differently, with families emphasizing emotional and social burdens and nurses focusing on medical management and resilience. Integrating both perspectives is critical for comprehensive care. Future studies should include children’s self-reports and larger samples to strengthen findings